2022
DOI: 10.3390/v14020230
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Broadly Neutralizing Monoclonal Antibody against SARS-CoV-2 Variants

Abstract: The constant mutation of SARS-CoV-2 has led to the emergence of new variants, which call for urgent effective therapeutic interventions. The trimeric spike (S) protein of SARS-CoV-2 is highly immunogenic with the receptor-binding domain (RBD) that binds first to the cellular receptor angiotensin-converting enzyme 2 (ACE2) and is therefore the target of many neutralizing antibodies. In this study, we characterized a broadly neutralizing monoclonal antibody (mAb) 9G8, which shows potent neutralization against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Strategies based on mutational scanning of the SARS-CoV-2 spike are not new. Others and us have shown that such approaches can be used to generate libraries containing individual mutations present in the Omicron, but not in the ancestral variants, and thus identify epitopes that escape recognition by monoclonal antibodies (16,17) and polyclonal sera (15,16,29). A very comprehensive mutational scanning based on the XBB.1.5 spike has been recently performed by the Bloom lab to introduce 9000 theoretical mutations on the XBB.1.5 background and thus predict future potential escape mutations (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies based on mutational scanning of the SARS-CoV-2 spike are not new. Others and us have shown that such approaches can be used to generate libraries containing individual mutations present in the Omicron, but not in the ancestral variants, and thus identify epitopes that escape recognition by monoclonal antibodies (16,17) and polyclonal sera (15,16,29). A very comprehensive mutational scanning based on the XBB.1.5 spike has been recently performed by the Bloom lab to introduce 9000 theoretical mutations on the XBB.1.5 background and thus predict future potential escape mutations (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, the contribution of single mutations to the immune escape of BA.2.86 remains unclear. Mutational scanning approaches, where libraries of viruses with single amino acid mutations in the spike protein are compared to the wild-type virus are powerful tools for the identification of epitopes recognized by monoclonal antibodies (15)(16)(17), but polyclonal serum antibodies recognize numerous epitopes simultaneously and redundantly. Therefore, mutating one out of 33 epitopes on an ancestral background may only marginally decrease the serum neutralizing activity if some among the remaining 32 epitopes are recognized by independent antibody clones.…”
Section: Introductionmentioning
confidence: 99%
“…161,162 Additionally, the susceptibility of mapped antibodies to new mutations can be measured, which in turn may forecast whether recently discovered mAbs are susceptible to viral escape. 163 Hence, by employing a pseudovirus neutralization experiment to use antibody-mediated neutralization, one can define functional antibodies against both individual and combined VOCs. 164 Hastie and the group structurally examined representative antibody binding and performed pseudovirus neutralization experiments to understand how S protein mutations affect antibody function, including various combinations of mutations seen in specific VOCs.…”
Section: Mapping the Susceptibility Of Global Antibodies Towards Epit...mentioning
confidence: 99%
“…By a thorough understanding of antibody footprints and their interaction with targets such as S protein, optimal blends of monoclonal antibodies can be identified to prevent and treat emergent VOCs infections such as omicron and deltacron (recombinant omicron plus delta) to diminish the danger of immune evasion 161,162 . Additionally, the susceptibility of mapped antibodies to new mutations can be measured, which in turn may forecast whether recently discovered mAbs are susceptible to viral escape 163 . Hence, by employing a pseudovirus neutralization experiment to use antibody‐mediated neutralization, one can define functional antibodies against both individual and combined VOCs 164 …”
Section: Mapping the Susceptibility Of Global Antibodies Towards Epit...mentioning
confidence: 99%